Depression and Anxiety in Patients with Maxillofacial Trauma Undergoing Reconstructive and Plastic Surgery - Imran Khan, Shakil Asif, Irfan Ishaq, Imran Saeed, Maria Batool Khan, Muhammad Hammad Saleem, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Maxillofacial trauma, resulting from accidents, violence, or congenital deformities, often has profound physical, emotional, and psychological effects. While reconstructive and plastic surgery focuses on restoring facial function and aesthetics, patients frequently experience elevated levels of depression and anxiety due to the psychological impact of their trauma. Methodology: This study investigates the prevalence and severity of depression and anxiety in 90 patients undergoing reconstructive and plastic surgery for maxillofacial trauma. The relationship between preoperative psychological status, the extent of facial injury, and postoperative psychological outcomes is analyzed. Results: Results indicate that a substantial proportion of patients experience significant depressive and anxiety symptoms, both before and after surgery, with a clear correlation between the severity of trauma and the intensity of psychological distress. Conclusion: These findings emphasize the importance of including psychological support as part of the multidisciplinary care for maxillofacial trauma patients. Keywords: Maxillofacial trauma, Reconstructive surgery, Plastic surgery, Depression, Anxiety, Psychological distress